Evaluation of Bioengineering Soil Erosion Control Techniques in Standard USLE Plots - Yong, Hong Liang (2000)
This erosion control study on Serdang series soil was conducted in standard Universal Soil Loss Equation (USLE) plots of 9% slope at the Department of Biological and Agricultural Engineering (DBAE) field station, Universiti Putra Malaysia (UPM). Rainfall was recorded with an automatic pluviometer. Runoff and soil losses were collected at the downslope in calibrated buckets. The first set of experiments (1/1/98 - 31/12/98) was carried out on 5 plots. These plots were treated with vetiver (Vetiveria zizanioides), legume (Arachis pintoi), spot turfing and close turfing (Axonopus compressus), respectively. A plot was left bare without vegetation as a control. Results showed that there were no significant differences on soil loss among the treatments with values less than 60 t/ha/y. The bare plot had significantly greater soil loss and runoff of 170 t/ha/y and 670 mm, respectively. There were no significant differences in runoff between the plots with legume and vetiver, vetiver and spot turfing and finally spot turfing and close turfing. The close turfing produced the lowest erosion losses with 99% and 90% less soil loss and runoff, respectively compared to the bare plot. The second set of experiments (115/98 - 30/4/99) was carried out on another 5 plots. The plots consisted of "coco-fibromat" + hydroseeding, hydroseeding + "fibromat", "fibromat" + hydro seeding, hydro seeding alone and "geojute + hydroseeding. Hydroseeding alone had significantly greater soil loss (4 t/ha/y) and runoff (170 mm) than other hydro seeding treatments « 0.8 t/ha/y and < 90 mm). The runoff depths between hydro seeding alone and "geojute" + hydro seeding was not significantly different. Hydroseeding anchored with "fibromat" resulted in lower soil loss and runoff, with 98.2% and 58.2% reduction, respectively compared to hydroseeding alone. The third set of experiments (11/11/98 - 31/11/99) was carried out on the 5 plots that were constructed later in September 1998. The plots were treated with bermudagrass (Cynodon daetylon), natural vegetation (Pennisetum purpureum), upland rice (Oryza sativa) and upland rice + "fibromat". A plot was left bare without vegetation as a control. The results revealed that they were no significant differences on soil loss among the treatments with values less than 55 t/ha/y. The bare plot had significantly greater soil loss and runoff of 125 t/ha/y and 597 mm, respectively. There was no significant difference in runoff between the bare plot and bermudagrass plot. The upland rice anchored with "fibromat" produced the lowest erosion losses with 99% and 98% reduction in soil loss and runoff, respectively compared to the bare plot. Treatments with biomats and close turfing gave the best protection against soil erosion with cover management factor lower than 0.0l. The highest correlation (r = 0.87) was obtained between the soil loss from the bare plots and KE>25.